(untitled) (Indian Journal of Arid Horticulture, 2013)
Ber (Ziziphus mauritiana Lamk.) is an economically important tropical fruit tree, which is grown all over the drier parts of the Indian subcontinent, Africa and northern Australia for its fresh fruits. It is one of the suitable trees to grow in dry regions, because it can withstand long periods of drought. Ber (Chinese date, Chinese Fig or bore) also known as poor man’s fruit is most widely cultivated in Punjab, Haryana, Rajasthan, Uttar Pradesh, Madhya Pradesh, Bihar, Gujarat, Maharashtra etc. Liu and Cheng (1995) reported that Indo-Malaysia region is the centre of both evolution and distribution of the genus Zizyphus. In India, a number of ber cultivars have been developed largely by the growers through selection in different regions. Maximum variability of ber is observed in Rajasthan, Gujarat, Haryana, Punjab and Madhya Pradesh and Uttar Pradesh. In Gujarat, Mehsana, Anand, Panchmahal, Patan and Sabarkatha districts are having rich diversity of ber(Shukla et al., 2003).